2019
DOI: 10.1007/s40430-019-1895-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal magnetorheological fluid particle loading and size for shear mode monotube damper

Abstract: Magnetorheological (MR) fluids belong to a class of controllable fluids, and the composition and concentration of its components govern its magnetorheological properties. In this study, an optimum particle loading (or mass fraction) and size of iron particles in MR fluid for use in a shear mode monotube MR damper were determined based on the damping force and off-state viscosity of synthesized MR fluid samples. Initially, the morphological and magnetic properties of carbonyl iron particles were characterized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…The mixing ratio used is 70% by volume of silicone oil and 30% by volume of CIP as this is found to be the ideal ratio for application in an automotive damper. 9 The criteria used for choosing this mixing ratio is the magnitude of the damping force developed for a given amount of current supplied. The yield stress developed by the MR fluid in the presence of a magnetic field increases when the proportion of CIP is increased.…”
Section: Synthesis Of the Mr Fluidmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixing ratio used is 70% by volume of silicone oil and 30% by volume of CIP as this is found to be the ideal ratio for application in an automotive damper. 9 The criteria used for choosing this mixing ratio is the magnitude of the damping force developed for a given amount of current supplied. The yield stress developed by the MR fluid in the presence of a magnetic field increases when the proportion of CIP is increased.…”
Section: Synthesis Of the Mr Fluidmentioning
confidence: 99%
“…The force developed due to the field-controlled yield stress (controllable force) F s is found using equation (9). The values of F s thus calculated are tabulated in Table 9.…”
Section: Mr Damper Modeling Based On Mr Fluid Rheology and Mr Damper mentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the six-layered CGRP-PMC material has high strength and stiffness compared to the two-and four-layered CGRP-PMC material. 17,26,27 The properties of CI p provided by the supplier are provided in Table 3 and that of silicone oil in Table 4. The MRF was characterized using Rheometer (Anton Paar, MCR 702) to determine the rheological properties and results were discussed in authors' previous article.…”
Section: Fabrication and Dynamic Characterization Of Cgrp-pmc-mrf Cormentioning
confidence: 99%
“…The effect of constituents of MRF such as particle size, weight fraction of carbonyl iron powder (CIP), base oil viscosity, additives on the performance of MR devices were investigated, such as MR dampers [23,24] MR brakes [25], MR rotary brakes [26] and the optimal composition of MRF which yielded best performance for those MR devices were determined. Romaszko et al [27] determined the vibration characteristics of MR beam filled with two types of commercial MRFs and concluded that weight fraction of iron particles in the fluid has a major effect on the natural frequency and damping coefficient of the beam.…”
Section: Introductionmentioning
confidence: 99%